PELATIHAN MERAMBAN DAN BUDIDAYA TANAMAN PANGAN ALTERNATIF UNTUK MENGHADAPI DAMPAK VIRUS CORONA - Tri Haryanto; Rumayya Rumayya; Shochrul Rohmatul Ajija; M. Khoerul Mubin (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2021)
The COVID-19 pandemic has caused residents of RT 01 / RW 01, Kelurahan Dukuh Pakis, Surabaya to face problems in the form of a decrease in residents' income and a potential shortage of foodstuffs due to the implementation of the lockdown policy (PSBB). The solution offered to mitigate this problem is to conduct training on the introduction and use of wild plants for food, as well as online assistance with botanists in developing wild food plant gardens on unused land located in the middle of residential areas. Online assistance is carried out using WhatsApp in residents’ groups. Apart from online assistance through WhatsApp, residents are also provided with modules in PDF format and an online learning video. This community development program is expected to give the residents of RT 01 / RW 01 Kelurahan Dukuh Pakis, Surabaya an insight into the benefits of wild plants as an alternative food source; ability to manage alternative plant cultivation independently or collectively; and realizing food self-sufficiency with various types of wild plants in anticipation of a food crisis due to the Corona virus. There are 4 (four) outputs from this program: 1) publication in an ISSN journal; 2) publication in print / electronic mass media; 3) online learning videos on the use of wild plants; and 4) availability of beneficial wild plant gardens as alternative food sources.